Muscle deficits with normal bone microarchitecture and geometry in young adults with well-controlled childhood-onset Crohn's disease. Issue 12 (December 2020) - Steell, Lewis; Johnston, Blair A.; Dewantoro, Dickson; Foster, John E.; Gaya, Daniel R.; Macdonald, Jonathan; McMillan, Martin; Russell, Richard K.; Seenan, John Paul; Ahmed, S. Faisal; Gray, Stuart R.; Wong, Sze Choong
Abstract : Background: Muscle–bone deficits are common in pediatric Crohn's disease; however, few studies have assessed long-term musculoskeletal outcomes in adults with childhood-onset Crohn's disease. This study assessed the prevalence of musculoskeletal deficits in young adults with childhood-onset Crohn's disease compared with healthy controls. Methods: High-resolution MRI and MR spectroscopy were used to assess bone microarchitecture, cortical geometry and muscle area, and adiposity at distal femur and bone marrow adiposity (BMA) at lumbar spine. Muscle function and biomarkers of the muscle-bone unit were also assessed. Results: Twenty-seven adults with Crohn's disease with median (range) age 23.2 years (18.0, 36.1) and 27 age and sex-matched controls were recruited. Trabecular microarchitecture, cortical geometry and BMA were not different between Crohn's disease and controls ( P  > 0.05 for all). Muscle area was lower ( P  = 0.01) and muscle fat fraction was higher ( P  = 0.04) at the distal femur in Crohn's disease compared to controls. Crohn's disease participants had lower grip strength [-4.3 kg (95% confidence interval (CI), -6.8 to -1.8), P  = 0.001] and relative muscle power [-5.0 W/kg (95% CI, -8.8 to -1.2), P  = 0.01]. Crohn's disease activity scores negatively associated with trabecular bone volume ( r  = -0.40, P  = 0.04) and muscle area ( r  = -0.41, P  = 0.03). Conclusion: Young adults with well-controlled Crohn's disease managed with contemporary therapies did not display abnormal bone microarchitecture or geometry at the distal femur but exhibited muscle deficits. The observed muscle deficits may predispose to musculoskeletal morbidity in future and interventions to improve muscle mass and function warrant investigation. Abstract : Supplemental Digital Content is available in the text.